Culture media affects accuracy of prediction of metallo-β-lactamases mediated resistance to imipenem - Kexuan Chen; Sarah Miller; Kristine Goy; Tina Lam; Marlène Maeusli; Rosemary She; Brad Spellberg; Brian Luna (PLoS ONE, 2026)
Metallo-β-lactamases (MBLs) hydrolyze the beta-lactam ring in beta-lactam antibiotics, rendering them ineffective. Infections caused by MBL-harboring bacteria result in higher mortality, more costs and prolonged hospital stays due to the limited treatment options. Recently, antimicrobial susceptibility testing using RPMI-1640 has been found to have more accuracy in predicting in vivo efficacy due to its zinc deficiency. We sought to expand the previous studies of accessing in vivo efficacy using zinc-limited media versus conventional media to more antimicrobial agents and MBL-producing strains. The susceptibility of isolates was determined by performing minimum inhibitory concentration (MIC) assays using traditional cation-adjusted Mueller Hinton broth (CAMHB) or zinc-limited media. In vivo outcomes were evaluated using the Galleria mellonella infection model and neutropenic mouse thigh infection model. The MICs of MBL-harboring strains decreased in zinc-limited media compared to in nutrient-rich media, suggesting susceptibility of a subset of resistant strains when tested in zinc-limited media. Notably, we observed statistically significant MICs decreasing against imipenem, which demonstrated the best efficacy among the six tested antibiotics. Additionally, the outcomes of in vivo tests in both the G. mellonella model and the mouse model were better predicted with in vitro MIC assays performing in zinc-limited media. The use of zinc-limited media may lead to increased accuracy of the prediction of in vivo efficacy of beta-lactams against MBL-harboring bacteria.